2015
DOI: 10.1111/ajad.12173
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of substance use disorders in American physicians

Abstract: Alcohol abuse or dependence is a significant problem among American physicians. Since prognosis for recovery of physicians from chemical dependency is exceptionally high, organizational approaches for the early identification of problematic alcohol consumption in physicians followed by intervention and treatment where indicated should be strongly supported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
196
5
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 324 publications
(222 citation statements)
references
References 39 publications
5
196
5
9
Order By: Relevance
“…This program was implemented in response to a resident suicide. 42 Investigation into the benefits of this program remain to be published, but is an important move towards helping surgeons deal with burnout and its dangerous consequences 13,14,43 …”
Section: Discussionmentioning
confidence: 99%
“…This program was implemented in response to a resident suicide. 42 Investigation into the benefits of this program remain to be published, but is an important move towards helping surgeons deal with burnout and its dangerous consequences 13,14,43 …”
Section: Discussionmentioning
confidence: 99%
“…Burnout has a significant impact on personal well‐being. In physicians, burnout is associated with an increase in alcohol use disorders, depression, and suicide . Burnout is also linked to stress‐related health outcomes, including headache, fatigue, gastrointestinal issues, musculoskeletal pain, hypertension, cardiovascular disease, and sleep disturbances .…”
Section: Impact Of Burnoutmentioning
confidence: 99%
“…Researchers have suggested that substance use in medical school may be the root of the ongoing problem of increased substance use in practicing physicians [8–10]. Hence, identifying the rates and risks of substance use and the social patterns that promote or inhibit use during medical education is an increasingly important task.…”
Section: Introductionmentioning
confidence: 99%